2016
DOI: 10.1007/s12028-016-0254-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Resistant Organisms and Clostridium difficile with Prolonged Systemic Antibiotic Prophylaxis for Central Nervous System Devices

Abstract: We found a higher incidence of resistant organisms in patients receiving prolonged antibiotic prophylaxis with a CNS device, but similar incidence of C. difficile compared to controls. Lack of data supporting prolonged antibiotic prophylaxis for CNS devices and the risk of nosocomial infections with resistant organisms encourage limiting prophylactic antibiotics to a short periprocedural course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The benefit of antibiotic prophylaxis beyond this time frame, however, is not clear and may be associated with increased complications such as infection with resistant organisms or C. diff [29]. In a study of patients with mostly TBI with EVDs or ICP monitors, and prophylactic antibiotic use in 73 % of the cohort, resistant organisms were more frequently found in the study versus control cohort; however, no significant difference was found in frequency of resistant organisms and C. diff rate when adjusting for ICU and hospital LOS and mechanical ventilation [30]. In contrary, limitation of systemic antimicrobial prophylaxis to the first 24 h after EVD placement in a single-center cohort significantly decreased the risk of C. diff infection without adverse effect on the rate of positive CSF cultures [29].…”
Section: Central Nervous System Devicesmentioning
confidence: 99%
“…The benefit of antibiotic prophylaxis beyond this time frame, however, is not clear and may be associated with increased complications such as infection with resistant organisms or C. diff [29]. In a study of patients with mostly TBI with EVDs or ICP monitors, and prophylactic antibiotic use in 73 % of the cohort, resistant organisms were more frequently found in the study versus control cohort; however, no significant difference was found in frequency of resistant organisms and C. diff rate when adjusting for ICU and hospital LOS and mechanical ventilation [30]. In contrary, limitation of systemic antimicrobial prophylaxis to the first 24 h after EVD placement in a single-center cohort significantly decreased the risk of C. diff infection without adverse effect on the rate of positive CSF cultures [29].…”
Section: Central Nervous System Devicesmentioning
confidence: 99%
“…Although antibiotic prophylaxis is currently a cornerstone of SSI prevention, prolonged antibiotic use has been associated with development of resistant organisms and increased SSI risk. In addition, previous antibiotic use is a risk factor for carriage of antibiotic‐resistant organisms, such as extended‐spectrum β‐lactamase‐producing Enterobacteriaceae, in surgical patients.…”
Section: Potential Of Anti‐s Aureus Vaccines To Address Increasing Amentioning
confidence: 99%
“…Prolonged systemic antibiotic prophylaxis increases the risk of developing resistant organisms in the central nervous system after implantation of medical devices. 10 Consequently, shorter perioperative courses of antibiotics are recommended. 10 A single topical application of vancomycin is expected to provide needed local prophylaxis for the surgical site while minimizing unnecessary systemic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…10 Consequently, shorter perioperative courses of antibiotics are recommended. 10 A single topical application of vancomycin is expected to provide needed local prophylaxis for the surgical site while minimizing unnecessary systemic exposure. We observed only 2 patients treated with topical vancomycin who exhibited slightly positive vancomycin serum levels (6.3 mg/ml), compared with those who received intravenous vancomycin (10.7 mg/ml).…”
Section: Discussionmentioning
confidence: 99%